Never give up : Dr. Kati Karikó and the race for the future of vaccines - Dadey, Debbie (Millbrook Press, 2023)
"This picture book biography introduces Hungarian American biochemist Katalin Karikó, who played a critical role in developing the mRNA vaccine for COVID-19. Follow the journey of Katalin (Kati) Karikó from her childhood in rural Hungary"--